2019
DOI: 10.3324/haematol.2018.208637
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of commonly used front-line regimens on survival outcomes in patients aged 70 years and older with acute myeloid leukemia

Abstract: Comparisons of commonly used frontline regimens on survival outcomes in patients age 70 years and older with acute myeloid leukemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
(39 reference statements)
4
31
0
2
Order By: Relevance
“…Single-center and small studies of older AML patients treated with HMAs have reported median OS estimates ranging from 8.0 to 14.4 months, which largely encompass the estimates provided in the largest phase 3 trials AZA-AML-001 and DACO-016. 10,13,14,[32][33][34] A meta-analysis of decitabine-treated, newly diagnosed AML patients aged $60 years reported a pooled median OS estimate of 8.1 months, though it should be noted that the analysis included several of the aforementioned single-center studies and data obtained from patients treated on nonstandard decitabine schedules. 35 Our study found an identical median survival estimate for azacitidine-treated patients (7.1 months), though a longer median survival for decitabine-treated patients (8.2 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-center and small studies of older AML patients treated with HMAs have reported median OS estimates ranging from 8.0 to 14.4 months, which largely encompass the estimates provided in the largest phase 3 trials AZA-AML-001 and DACO-016. 10,13,14,[32][33][34] A meta-analysis of decitabine-treated, newly diagnosed AML patients aged $60 years reported a pooled median OS estimate of 8.1 months, though it should be noted that the analysis included several of the aforementioned single-center studies and data obtained from patients treated on nonstandard decitabine schedules. 35 Our study found an identical median survival estimate for azacitidine-treated patients (7.1 months), though a longer median survival for decitabine-treated patients (8.2 months).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Results from controlled retrospective analyses suggested that OS for some older AML patients who received HMAs might be similar, or even superior, to those who received intensive therapy. 14 The toxicity and mortality associated with intensive chemotherapy and the lack of alternative nonintensive therapies for older AML patients resulted in the adoption of HMAs as the de facto standard of care for this population. [10][11][12][13]15 A prior Surveillance, Epidemiology and End Results (SEER)-Medicare study reported that among older AML patients diagnosed in [2005][2006][2007]10.7% patients were treated with a frontline HMA.…”
Section: Introductionmentioning
confidence: 99%
“…Hypomethylating agents (HMAs) are increasingly used in patients with acute myeloid leukaemia (AML). Still, the benefit of HMAs compared to conventional therapy is debated and results differ between studies (Kantarjian et al , ; Quintas‐Cardama et al , ; Bories et al , ; Dombret et al , ; Almeida et al , ; Maurillo et al , ; Talati et al , ). In the present study, we report data on the use and benefit of HMAs from a large population‐based cohort covering all elderly patients in Sweden during a 10‐year period.…”
mentioning
confidence: 99%
“…Recently, Talati et al . reported that patients aged ≥70 years treated with HMA had superior OS compared to both intensive and palliative treatment regimens (Talati et al , ). In order to investigate if our present results would show similar results in patients aged ≥70 years, we performed a PSM analysis in patients aged ≥70 years, but found the same results with no significant differences between HMA and IC (data not shown).…”
mentioning
confidence: 99%
“…Poorer performance status itself has been shown to be an unfavorable prognostic factor in patients with AML, associated with increase in both short and long term mortality [28]. Patients with AML-MRC, given their older age, higher number of comorbidities, and lower performance statuses, tend to be less likely treated with curative intent intensive chemotherapy regimens as compared to younger patients [31].…”
Section: Advanced Agementioning
confidence: 99%